2020
DOI: 10.1055/a-0981-6286
|View full text |Cite
|
Sign up to set email alerts
|

The Change in Attitudes Towards Abortion in Former West and East Germany After Reunification: A Latent Class Analysis and Implications for Abortion Access

Abstract: Introduction The legal status of abortion has changed in the regions of former East Germany after reunification due to the adoption of restrictive West German abortion policies. The aim of this study was to evaluate the impact on attitudes towards abortion and the associated health care implications in Western and Eastern Germany. Materials and Methods Nationally representative data on public support for legally restricting abortion access were taken from the German General Social Survey and included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Using LCA, this population-based study of reproductive-age women uncovered three distinct profiles of support for legal abortion services in Zambia; two of these groups clustered exclusively around support of (legal abortion advocates, ∼23 percent prevalence) and opposition to (legal abortion opponents, ∼58 percent prevalence) pregnancy termination irrespective of grounds for abortion-seeking, while the third (conditional supporters of legal abortion, ∼19 percent prevalence) consisted of women who support legal abortion services in circumstances where continuing the pregnancy would threaten the life of the mother or fetus. These findings complement emerging evidence from the United States (Osborne et al 2022) and Germany (Hanschmidt et al 2020), where studies have found that conditional support for legal abortion services (primarily in circumstances where maternal/fetal health is compromised) persists amidst highly polarized attitudes, specifically universal support or objection, towards legalized abortion. Even in the presence of a relatively progressive legal framework, these results reaffirm globally observed discrepancies between public attitudes towards legalized abortion and the broader legal environments governing abortion care provision (Scoglio and Nayak 2023;Smith et al 2022).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Using LCA, this population-based study of reproductive-age women uncovered three distinct profiles of support for legal abortion services in Zambia; two of these groups clustered exclusively around support of (legal abortion advocates, ∼23 percent prevalence) and opposition to (legal abortion opponents, ∼58 percent prevalence) pregnancy termination irrespective of grounds for abortion-seeking, while the third (conditional supporters of legal abortion, ∼19 percent prevalence) consisted of women who support legal abortion services in circumstances where continuing the pregnancy would threaten the life of the mother or fetus. These findings complement emerging evidence from the United States (Osborne et al 2022) and Germany (Hanschmidt et al 2020), where studies have found that conditional support for legal abortion services (primarily in circumstances where maternal/fetal health is compromised) persists amidst highly polarized attitudes, specifically universal support or objection, towards legalized abortion. Even in the presence of a relatively progressive legal framework, these results reaffirm globally observed discrepancies between public attitudes towards legalized abortion and the broader legal environments governing abortion care provision (Scoglio and Nayak 2023;Smith et al 2022).…”
Section: Discussionsupporting
confidence: 76%
“…2022) and Germany (Hanschmidt et al. 2020), where studies have found that conditional support for legal abortion services (primarily in circumstances where maternal/fetal health is compromised) persists amidst highly polarized attitudes, specifically universal support or objection, towards legalized abortion. Even in the presence of a relatively progressive legal framework, these results reaffirm globally observed discrepancies between public attitudes towards legalized abortion and the broader legal environments governing abortion care provision (Scoglio and Nayak 2023; Smith et al.…”
Section: Discussionmentioning
confidence: 99%
“…The care situation of women with an unintended pregnancy is recently an important topic within political healthcare discussions in Germany. 1 2 The high relevance is reflected by several cases of lawsuits against the current legal regulations on abortion rights [2][3][4][5][6] as well as a reduction of the number of medical institutions performing abortions of almost 50% from 2003 to 2012 in Germany. 7 The federal statistical office counted 100 000 abortions per year for the past 10 years.…”
Section: Introductionmentioning
confidence: 99%